Anesthesia reduces discharge rates in the human pallidum without changing the discharge rate ratio between pallidal segments. (13th October 2016) - Castrioto, Anna; Marmor, Odeya; Deffains, Marc; Willner, Dafna; Linetsky, Eduard; Bergman, Hagai; Israel, Zvi; Eitan, Renana; Arkadir, David
Abstract: Classical rate models of basal ganglia circuitry associate discharge rate of the globus pallidus external and internal segments (GPe, GPi respectively) solely with dopaminergic state and predict an inverse ratio between the discharge rates of the two pallidal segments. In contrast, the effects of other rate modulators such as general anesthesia (GA) on this ratio have been ignored. To respond to this need, we recorded the neuronal activity in the GPe and GPi in awake and anesthetized human patients with dystonia (57 and 53 trajectories respectively) and in awake patients with Parkinson's disease (PD, 16 trajectories) undergoing deep brain stimulation procedures. This triad enabled us to dissociate pallidal discharge ratio from general discharge modulation. An automatic offline spike detection and isolation quality system was used to select 1560 highly isolated units for analysis. The mean discharge rate in the GPi of awake PD patients was dramatically higher than in awake dystonia patients although the firing rate in the GPe was similar. Firing rates in dystonic patients under anesthesia were lower in both nuclei. Surprisingly, in all three groups, GPe firing rates were correlated with firing rates in the ipsilateral GPi. Thus, the firing rate ratio of ipsilateral GPi/GPe pairs was similar in awake and anesthetized patients with dystonia and significantly higher in PD. We suggest that pallidal activity is modulated by at least two independent processes: dopaminergic state which changes the GPi/GPe firing rate ratio, and anesthesia which modulates firing rates in both pallidal nuclei without changing the ratio between their firing rates. Abstract : The neuronal activity in the pallidum of awake and anesthetized human patients with dystonia and of awake patients with Parkinson's disease suggests that pallidal activity is modulated by at least two independent processes. The first, the dopaminergic state which changes the GPi/GPe firing rate ratio. The second, anesthesia (or state of arousal) which modulates firing rates in both pallidal nuclei without changing the ratio between their firing rates.